2015
DOI: 10.1007/s12010-015-1611-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipozyme TL IM as Catalyst for the Synthesis of Eugenyl Acetate in Solvent-Free Acetylation

Abstract: The ability of commercial immobilized lipase from Thermomyces lanuginosus (Lipozyme TL IM) to catalyze the acetylation of essential clove oil with acetic anhydride in a solvent-free system was studied, and the antimicrobial activity of the ester formed was evaluated as well. Experimental design based on two variables (eugenol to acetic anhydride molar ratio and temperature) was employed to evaluate the experimental conditions of eugenyl acetate ester production. The maximum conversion yield (92.86 %) was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…Having demonstrated that the unprecedented synthesis of eugenyl isobutyrate can be efficiently achieved in continuous‐flow mode with the aid of Novozym 435 or Lipozyme RM IM packed‐bed microreactors, we also verified the efficiency of the same experimental set‐up for eugenyl acetate synthesis. We were encouraged in doing this by previous works that described the enzymatic synthesis of eugenyl acetate under batch and continuous‐flow mode in solvent‐free systems with experimental conditions (substrate molar ratio and temperature) very similar to those determined in this work . Thus, we conducted the tests to assess the operational stability of both the Novozym 435 and Lipozyme RM IM microreactors using an eugenol/acetic anhydride molar ratio of 1 : 5, a feed flow rate of 8 μL min −1 , and a temperature of 68 °C.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Having demonstrated that the unprecedented synthesis of eugenyl isobutyrate can be efficiently achieved in continuous‐flow mode with the aid of Novozym 435 or Lipozyme RM IM packed‐bed microreactors, we also verified the efficiency of the same experimental set‐up for eugenyl acetate synthesis. We were encouraged in doing this by previous works that described the enzymatic synthesis of eugenyl acetate under batch and continuous‐flow mode in solvent‐free systems with experimental conditions (substrate molar ratio and temperature) very similar to those determined in this work . Thus, we conducted the tests to assess the operational stability of both the Novozym 435 and Lipozyme RM IM microreactors using an eugenol/acetic anhydride molar ratio of 1 : 5, a feed flow rate of 8 μL min −1 , and a temperature of 68 °C.…”
Section: Resultsmentioning
confidence: 94%
“…We were encouraged in doing this by previous works that described the enzymatic synthesis of eugenyl acetate under batch and continuous-flow mode in solventfree systems with experimental conditions (substrate molar ratio and temperature) very similar to those determined in this work. [11][12][13]15 Thus, we conducted the tests to assess the operational stability of both the Novozym 435 and Lipozyme RM IM microreactors using an eugenol/acetic anhydride molar ratio of 1 : 5, a feed flow rate of 8 μL min −1 , and a temperature of 68 °C. Figure 5 Most of the experimental works on esterification synthesis have shown that acetates have no kind of inhibition on lipases, no matter the type of lipase.…”
Section: Operational Stability Of Novozym 435 and Lipozyme Rm Im Rementioning
confidence: 99%
See 2 more Smart Citations
“…Eugenyl acetate is an ester that can be used as antimicrobial agent (Silva et al 2015;Chiaradia et al 2012), anticancerous (Carrasco et al 2008), acaricide (Pasay et al 2010), growth inhibitor of Aedes aegypti mosquito that transmits dengue (Pandey et al 2013), prevent teeth decalcification (Marya et al 2012) and may be employed as additive in biofuels (Kadarohman et al 2012). Besides, eugenyl acetate forms part of the European Union database and is authorized for use in food.…”
Section: Introductionmentioning
confidence: 99%